Draft Annual Plan 1980-81 Volume I Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1980)
The Annual Plan for the year 1979-80 was approved by the Planning Commission at Rs. 11000 .00 lacs. In consequence of the decisions taken by the National Development Council a number of Centrally sponsor Schemes have been transferred to the State Sector and in many cases the pattern of cost sharing the State Sector and in many cases the pattern of cost sharing between the Centre and the State has aIso been changed. To meet the additional liability on this account the State Government has been provided an amount of Rs. 720.00 lakhs in addition to the approved outlay. We have also received advance Plan assistance totaling Rs. 200.00 lacs in 100.00 lakhs for Rural road, Rs. 50.00 lacs for Minor, Irrigation and Rs. 50.00 lakhs far rural water supply schemes - to accelerate the pace of implementation of the on-going schemes and to take up new schemes in the drought/hailstorm effected areas. "
Government of Jammu and Kashmir
Planning And Development Department Jammu
Keywords: Animal Husbandry; Sheep Husbandry; Directorate of Soil Conservation; Minor Irrigation; Major and Medium Irrigation; Flood Control measures; Renovation of Joinery Mills; Expansion of Spinning Mills; Modernization of old Woolen Mills